2013
DOI: 10.1186/1475-925x-12-93
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive evaluation of energy loss in the pulmonary arteries using 4D phase contrast MR measurement: a proof of concept

Abstract: BackgroundThe repair surgery of congenital heart disease (CHD) associated with the right ventricular (RV)-pulmonary artery (PA) pathophysiology often left patients with critical post-operative lesions, leading to regurgitation and obstruction in the PAs. These lesions need longitudinal (with time) assessment for monitoring the RV function, in order for patients to have appropriate treatment before irreversible RV dysfunction occurs. In this research, we computed energy loss in the branch PAs using blood flow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…10,20,21 The development of 4D flow magnetic resonance imaging has provided a noninvasive method of collecting 4D velocity data needed to determine pressure, flow, and energy measurements throughout the cardiac cycle. 19 Noninvasive measurements of KE in the LV and RV were first described in prior studies utilizing 4D flow acquisitions and were thought to provide a nondirectional measure of the amount of work invested in overcoming the inertia of intracardiac blood during the cardiac cycle. 12,22 Although KE comprises only approximately 1% of the total LV work and 6% of total RV work at rest, 10,22 it plays a larger role in the myocardial work under exercise conditions than at rest.…”
Section: Discussionmentioning
confidence: 99%
“…10,20,21 The development of 4D flow magnetic resonance imaging has provided a noninvasive method of collecting 4D velocity data needed to determine pressure, flow, and energy measurements throughout the cardiac cycle. 19 Noninvasive measurements of KE in the LV and RV were first described in prior studies utilizing 4D flow acquisitions and were thought to provide a nondirectional measure of the amount of work invested in overcoming the inertia of intracardiac blood during the cardiac cycle. 12,22 Although KE comprises only approximately 1% of the total LV work and 6% of total RV work at rest, 10,22 it plays a larger role in the myocardial work under exercise conditions than at rest.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al studied the rates of pressure-flow and KE transferred between the branch PA and the MPA, as well as flow resistance due to MPA bifurcation, also relations derived from the Navier—Stokes equations. They showed that patients with congenital heart disease had considerably increased energy loss in the branch PAs compared to normal subject with normal PA physiology [ 36 ]. Besides energy loss, a modification in the 4D flow technique with asymmetrical 4-point motion encoding has allowed measurement of irreversible pressure loss through characterization of turbulent KE (34).…”
Section: Discussionmentioning
confidence: 99%
“…In order to analyse the reduction in flow resistance caused by the stenting operations, the kinetic energy loss (assuming negligible gravitational effect) in the system was analysed, similarly to the approach used by Lee et al (2013). The rate of kinetic energy loss (KE) at each boundary i at each time instance is given byK…”
Section: Kinetic Energymentioning
confidence: 99%